2010
DOI: 10.1371/journal.pbio.1000521
|View full text |Cite|
|
Sign up to set email alerts
|

WRAP53 Is Essential for Cajal Body Formation and for Targeting the Survival of Motor Neuron Complex to Cajal Bodies

Abstract: The WRAP53 protein regulates the formation and maintenance of Cajal bodies (nuclear sub-organelles), as well as directs the recruitment of nuclear factors to Cajal bodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
182
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(189 citation statements)
references
References 35 publications
7
182
0
Order By: Relevance
“…39,[44][45][46][47] WRAP53 interacts with coilin, providing the mechanistic link between telomerase and coilin. 48,49 Telomerase RNA localization to CBs was suggested to be important for telomerase function and mislocalization of telomerase RNA from CBs correlates with reduced telomerase activity. 45,50,51 In addition, coilin depletion by siRNA inhibits association of telomerase with telomeres.…”
Section: Coilin Historymentioning
confidence: 99%
“…39,[44][45][46][47] WRAP53 interacts with coilin, providing the mechanistic link between telomerase and coilin. 48,49 Telomerase RNA localization to CBs was suggested to be important for telomerase function and mislocalization of telomerase RNA from CBs correlates with reduced telomerase activity. 45,50,51 In addition, coilin depletion by siRNA inhibits association of telomerase with telomeres.…”
Section: Coilin Historymentioning
confidence: 99%
“…90 Similarly, depletion of other factors involved in small RNP biogenesis, such as Tgs1, WDR79/WRAP53, PHAX, INTS4 and USPL1 also cause Cajal bodies to disassemble. [91][92][93][94][95] In addition to overall protein levels, post-translational modifications (PTMs) of resident proteins, including SMN and coilin, are almost certainly important for establishing and maintaining inter-and intra-molecular interactions within Cajal bodies. [96][97][98][99][100] Disruption of these PTMs can result in mislocalization of SMN and alterations in Cajal body integrity.…”
Section: Inter-and Intra-molecular Interactions Within the Cajal Bodymentioning
confidence: 99%
“…At least 17 variants of this gene were identified, generated through alternative splicing as well as three different transcription start sites. So far, the reported function of the WRAP53 protein is without obvious relation to p53 (Mahmoudi et al, 2010), but it has been reported that exon 1a of the WRAP53 mRNA contributes to the induction of p53 in response to DNA damage. In Figure 5a, the 10 transcripts listed in the Ensembl database were aligned with the TP53 gene.…”
Section: Chemotherapeutic Drugs Differentially Induce Mutant P53 Levelsmentioning
confidence: 99%